Regional Policy Coherence for The Great Green Wall Initiative: Exploring Alignment of the AU Great Green Wall Initiative Strategy with the AU Biodiversity Strategy and Action Plan and the AU Green Recovery Action Plan - African Union (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This policy brief explores how enhanced policy coherence among three flagship African Union strategies - the Great Green Wall Initiative (GGWI) Strategy and Ten-Year Implementation Framework (2024–2034), the Biodiversity Strategy and Action Plan (2023–2030), and the Green Recovery Action Plan (2021–2027) - can significantly advance biodiversity conservation, land restoration, and climate resilience across Africa. It highlights key areas of alignment, including the promotion of nature-based solutions, sustainable land and water management, and integrated ecosystem restoration. Central to the GGWI Strategy is the scaling up of nature-based practices that create resilient value chains supporting biodiversity and local livelihoods. The brief also underscores the importance of equity and gender-transformative approaches, the integration of Indigenous knowledge systems, and inclusive benefit-sharing mechanisms to ensure socially just and effective conservation outcomes. Furthermore, the brief emphasises strengthening multisectoral engagement and aligning national and regional strategies - including National Biodiversity Strategies and Action Plans - to foster coordinated implementation. Mobilising public and private investment and establishing strategic partnerships with global biodiversity and climate networks are also identified as critical enablers. By embedding biodiversity as a core criterion for country participation and promoting cross-sectoral collaboration, the GGWI and aligned strategies can accelerate progress toward the Kunming-Montreal Global Biodiversity Framework, the Sustainable Development Goals, and broader climate and development goals.